Liquid crystal alignment agent, liquid crystal alignment film, and liquid crystal display element

The use of aromatic compounds in a liquid crystal alignment agent addresses the challenges of voltage retention and liquid crystal alignment in harsh environments, specifically preventing seizure in IPS and FFS drive systems.

JP7667535B2Active Publication Date: 2025-04-23NISSAN CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024093465
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-07
Filing Date
2024-06-10
Publication Date
2025-04-23
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

Existing liquid crystal alignment methods, particularly photoalignment, face challenges in maintaining high voltage retention rates in harsh environments and ensuring sufficient liquid crystal alignment, especially in IPS and FFS drive systems, where seizure can occur.

Method used

A liquid crystal alignment agent containing aromatic compounds with specific chemical structures, represented by formula (1), is used to enhance voltage retention and improve liquid crystal alignment, thereby preventing seizure in liquid crystal display devices.

Benefits of technology

The proposed solution achieves high voltage retention rates and good liquid crystal alignment even in harsh environments, effectively suppressing seizure in liquid crystal display devices using IPS or FFS drive systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667535000001
    Figure 0007667535000001
  • Figure 0007667535000002
    Figure 0007667535000002
  • Figure 0007667535000003
    Figure 0007667535000003
Patent Text Reader

Abstract

To provide a liquid crystal alignment agent for obtaining a liquid crystal display element that, even during alignment treatment using a photo-alignment technique that causes chemical changes through irradiation with radiation or the like, maintains a high voltage holding rate in harsh environments, exhibits good liquid crystal alignment properties, and can inhibit burn-in that occurs in IPS or FFS-type liquid crystal display elements; a liquid crystal alignment film; and a liquid crystal display element.SOLUTION: A liquid crystal alignment agent comprises an aromatic compound with two or more structures represented by the formula (1). (R is a hydrogen atom or a methyl group. Any hydrogen atom on a benzene ring is optionally substituted with a hydroxy group, a halogen atom, an alkyl group having 1-6 carbon atoms, an alkoxy group having 1-6 carbon atoms, or a monovalent organic group containing a fluorine atom and having 1-6 carbon atoms).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal aligning agent, a liquid crystal alignment film obtained from the liquid crystal aligning agent, a liquid crystal display device using the liquid crystal alignment film, and a novel compound used in the liquid crystal aligning agent. [Background technology]

[0002] Conventionally, various driving methods have been developed for liquid crystal display elements, which differ in electrode structure and physical properties of the liquid crystal molecules used, and various display elements are known, such as TN (Twisted Nematic) type, STN (Super Twisted Nematic) type, VA (Vertical Alignment) type, IPS (In-Plane Switching) type, FFS (Finge Field Switching) type, etc. These liquid crystal display elements generally have a liquid crystal alignment film for aligning the liquid crystal molecules.

[0003] Known materials for liquid crystal alignment films include polymers such as polyamic acid, polyamic acid ester, polyimide, polyamide, etc. Currently, the liquid crystal alignment film that is most widely used industrially is produced by rubbing the surface of a film formed on an electrode substrate using a polymerizable composition containing the above polymer in one direction with a cloth such as cotton, nylon, or polyester, a so-called rubbing treatment.

[0004] Rubbing treatment is an industrially useful method that is simple and has excellent productivity. However, as liquid crystal display elements become higher in performance, definition, and size, various problems occur during the rubbing treatment, such as scratches on the surface of the alignment film, dust generation, effects of mechanical force and static electricity, and non-uniformity within the alignment treatment surface.

[0005] As an alternative to rubbing treatment, a photo-alignment method is known in which liquid crystal alignment ability is imparted by irradiation with polarized radiation. As liquid crystal alignment treatments using the photo-alignment method, methods utilizing photoisomerization reactions, photocrosslinking reactions, photodecomposition reactions, and the like have been proposed (see Non-Patent Document 1). Patent Document 1 proposes using a polyimide film having an alicyclic structure such as a cyclobutane ring in the main chain in the photo-alignment method.

[0006] The photoalignment method described above is attracting attention as a promising liquid crystal alignment method because it is a rubbing-less alignment treatment method that can be produced using a simple industrial manufacturing process and is also expected to improve the contrast and viewing angle characteristics of liquid crystal display elements using IPS and FFS driving methods compared to liquid crystal alignment films obtained using rubbing treatment methods. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 9-297313 [Non-patent literature]

[0008] [Non-Patent Document 1] "Liquid Crystal Photo-Alignment Film" Kidowaki, Ichimura, Functional Materials, November 1997, Vol. 17, No. 11, pp. 13-22 Summary of the Invention [Problem to be solved by the invention]

[0009] In recent years, the scope of use of liquid crystal display elements has expanded, and liquid crystal display elements may be used for long periods of time in high temperature and high humidity environments or in environments exposed to light irradiation. A liquid crystal alignment film is required to be able to withstand use in such harsh environments, and a high voltage retention rate is one of its important characteristics. However, according to the findings of the present inventors, it has become clear that in the case of a photo-alignment method in which a chemical change occurs due to irradiation with radiation or the like, the voltage retention rate tends to decrease. In addition, it has become clear that when alignment ability is imparted by the photo-alignment method, the liquid crystal alignment property is insufficient, and for example, image sticking becomes a problem in liquid crystal display elements of an IPS driving method or an FFS driving method.

[0010] Therefore, the present invention aims to provide a liquid crystal alignment agent for obtaining a liquid crystal display element that has a high voltage retention rate and good liquid crystal alignment properties even in harsh environments, even in the case of alignment treatment using a photo-alignment method that causes chemical changes due to exposure to radiation, etc., and that can suppress burn-in that occurs in IPS drive type or FFS drive type liquid crystal display elements, a liquid crystal alignment film obtained from the liquid crystal alignment agent, a liquid crystal display element having the liquid crystal alignment film, and further a novel compound for use in the liquid crystal alignment agent. [Means for solving the problem]

[0011] As a result of intensive research, the present inventors have found that the above object can be achieved by a liquid crystal alignment agent containing, as an additive, an aromatic compound having a specific chemical structure as shown below, and have completed the present invention. The present invention relates to a liquid crystal aligning agent characterized by containing an aromatic compound having two or more structures represented by the following formula (1), a liquid crystal alignment film obtained from the liquid crystal aligning agent, a liquid crystal display device having the liquid crystal alignment film, and further, a novel compound used in the liquid crystal aligning agent. [ka] In the formula, R is a hydrogen atom or a methyl group, and any hydrogen atom on the benzene ring may be substituted with a hydroxyl group, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, or a monovalent organic group having 1 to 6 carbon atoms and containing a fluorine atom. Effect of the Invention

[0012] According to the present invention, even in the case of alignment treatment using a photoalignment method in which chemical changes occur due to exposure to radiation or the like, a liquid crystal alignment agent for obtaining a liquid crystal display element that has a high voltage retention rate and good liquid crystal alignment properties even in harsh environments, and in particular can suppress image sticking even in the IPS driving mode or FFS driving mode, a liquid crystal alignment film obtained from the liquid crystal alignment agent, a liquid crystal display element having the liquid crystal alignment film, and further a novel compound for use in the liquid crystal alignment agent are provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Aromatic compound of formula (1)> The liquid crystal aligning agent of the present invention is characterized in that it contains an aromatic compound having two or more structures represented by the following formula (1) (hereinafter, sometimes referred to as the aromatic compound of formula (1)). [ka]

[0014] R in the above formula (1) represents a hydrogen atom or a methyl group. Any hydrogen atom on the benzene ring may be substituted with a hydroxyl group, a halogen atom, an alkyl group having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms, or a monovalent organic group having 1 to 6 carbon atoms, preferably 1 to 4 carbon atoms, and containing a fluorine atom. Here, examples of the monovalent organic group having a fluorine atom include a trifluoromethyl group, a trifluoroethyl group, a trifluoromethoxy group, and a trifluoroethoxy group.

[0015] In the liquid crystal alignment agent of the present invention, by containing the aromatic compound of the above formula (1) as an additive, as specifically illustrated in the examples described later, even in the case of alignment treatment by a photo-alignment method in which a chemical change occurs due to irradiation with radiation, etc., a liquid crystal alignment film in a liquid crystal display element having a high voltage holding ratio and good liquid crystal alignment property under harsh environments can be obtained. Although the mechanism is not necessarily clear, it is generally considered as follows. In the alignment treatment by the photo-alignment method, for example, the surface of a film-like material formed from a liquid crystal alignment agent on the surface of a substrate is irradiated with nearly linearly polarized high-energy UV light. In this case, the irradiation of UV light produces decomposition products of the organic matter that constitutes the film-like material, which become impurities that cause a decrease in the voltage retention rate in the liquid crystal alignment film, and thus it is believed that the voltage retention rate of the liquid crystal alignment film is reduced. However, in the liquid crystal aligning agent of the present invention, when the above-mentioned impurities are generated by irradiation with UV light, the aromatic compound of the above formula (1) has a functional group capable of reacting with the impurities, and this reacts with the impurities that cause a decrease in the voltage holding ratio, thereby reducing the impurities contained in the obtained liquid crystal alignment film. Therefore, the liquid crystal alignment film obtained from the liquid crystal aligning agent of the present invention is believed to maintain a high voltage holding ratio. In addition, the aromatic compound of the formula (1) contained in the liquid crystal alignment agent of the present invention has a highly planar structure, so that the liquid crystal alignment of the obtained liquid crystal alignment film is not hindered, and a liquid crystal alignment film having high liquid crystal alignment is obtained. Therefore, in the IPS driving method or FFS driving method, even when the liquid crystal display element is driven for a long time, the liquid crystal returns to the same state as before the driving, so that a liquid crystal display element with less image sticking is obtained.

[0016] The aromatic compound of the above formula (1) is preferably a compound represented by the following formula (b1). [ka] In the above formula (b1), R has the same meaning as in the above formula (1). n is an integer of 2 to 6, when n is 2, A represents a single bond or a divalent linking group, and when n is 3 to 6, A represents an n-valent organic group.

[0017] Examples of the n-valent organic group include an n-valent hydrocarbon group, an n-valent heteroatom-containing group containing a group having a heteroatom between the carbon atoms of the hydrocarbon group or at the end of the hydrocarbon group, and an n-valent organic group in which some or all of the hydrogen atoms of the hydrocarbon group and the heteroatom-containing group are substituted with substituents. Examples of the divalent linking group for A include divalent hydrocarbon groups, divalent heteroatom-containing groups containing a group having a heteroatom between the carbon atoms of the hydrocarbon group or at the end of the hydrocarbon group, divalent linking groups in which some or all of the hydrogen atoms of the hydrocarbon groups and heteroatom-containing groups have been substituted with substituents, -S(=O)2-, -CO-, -O-, -S-, -NR-CO- (R represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), -NR-CO-NR- (R represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), and the like.

[0018] Examples of the n-valent hydrocarbon group include an n-valent group obtained by removing n hydrogen atoms from a hydrocarbon selected from the group consisting of alkanes having 1 to 30 carbon atoms, such as methane, ethane, propane, and butane; alkenes such as ethylene, propylene, butylene, and pentene; alkynes such as ethyne, propyne, butyne, and pentyne; alicyclic hydrocarbons having 3 to 30 carbon atoms, such as cycloalkanes such as cyclopropane, cyclobutane, cyclopentane, cyclohexane, norbornane, and adamantane; cycloalkenes such as cyclopropene, cyclobutene, cyclopentene, cyclohexene, and norbornene; aromatic hydrocarbons having 6 to 30 carbon atoms, such as benzene, toluene, xylene, mesitylene, naphthalene, methylnaphthalene, dimethylnaphthalene, and anthracene; and hydrocarbons in which some of the carbon-carbon bonds of the above-mentioned chain hydrocarbons have been replaced with the above-mentioned alicyclic hydrocarbons or aromatic hydrocarbons. Examples of the divalent hydrocarbon group include divalent groups obtained by removing two hydrogen atoms from the above-mentioned examples of the n-valent hydrocarbon groups.

[0019] Examples of the group having a hetero atom include a group having at least one atom selected from the group consisting of an oxygen atom, a nitrogen atom, a silicon atom, a phosphorus atom, and a sulfur atom. Specific examples include -O-, -NR- (wherein R represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms), -CO-, -S-, -CO-, and groups formed by combining these. Among these, -O- is preferred.

[0020] Examples of the substituent include halogen atoms such as a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom; alkoxy groups such as a methoxy group, an ethoxy group, and a propoxy group; alkoxycarbonyl groups such as a methoxycarbonyl group and an ethoxycarbonyl group; alkoxycarbonyloxy groups such as a methoxycarbonyloxy group and an ethoxycarbonyloxy group; a cyano group, a nitro group, and the like. In the above formula (b1), n ​​is preferably 2, and A is preferably a single bond or a divalent linking group.

[0021] The divalent linking group is preferably one having a structure represented by the following formula (a-1) or (a-2). [ka] In the above formulas (a-1) and (a-2), R1, R 1’ , R2, R 2’ each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, preferably 1 or 2 carbon atoms. each of m1 and m2 independently represents an integer of 1 to 18, preferably 1 to 6. n represents an integer of 1 to 6, preferably 1 to 4. In addition, "*" represents a bond.

[0022] From the viewpoint of increasing the reactivity with decomposition products generated in the photoalignment method, the aromatic compound of the above formula (1) preferably has a molecular weight of 2000 or less, more preferably 1500 or less. On the other hand, from the viewpoint of suppressing sublimation of the aromatic compound due to firing, the molecular weight of the above aromatic compound is preferably 150 or more, more preferably 200 or more.

[0023] Preferred examples of the aromatic compound of the above formula (1) include compounds selected from the group consisting of the following formulae (b-1) to (b-7): The compounds of the following formulae (b-1) to (b-4) are novel compounds not disclosed in the prior art. [ka]

[0024] <Polymer> The liquid crystal aligning agent of the present invention, which contains the aromatic compound of the above formula (1), contains a polymer capable of aligning liquid crystals, similar to known ones, but such a polymer is not particularly limited as long as it has the ability to align liquid crystals. Examples of such polymers include polyimide precursors, polyimides which are imidized products of polyimide precursors, acrylic polymers, methacrylic polymers, acrylamide polymers, methacrylamide polymers, polystyrene, polysiloxane, polyamide, polyester, polyurethane, polycarbonate, polyurea, polyphenol (novolac resin), maleimide polymers, and polymers into which a compound having an isocyanuric acid skeleton or a triazine skeleton has been introduced. Such polymers can be used alone or in combination of two or more.

[0025] The raw materials for producing these polymers include the following. When the polymer is a polyimide precursor or a polyimide such as a polyamic acid or a polyamic acid ester, at least one tetracarboxylic acid component selected from tetracarboxylic acids or derivatives thereof and a diamine; When the polymer is a (meth)acrylic polymer, it is (meth)acrylic acid or a derivative thereof, or a (meth)acrylic acid ester or a derivative thereof; when the polymer is a (meth)acrylamide polymer, it is (meth)acrylamide or a derivative thereof;

[0026] When the polymer is polystyrene, styrene or a derivative thereof is used; when the polymer is polysiloxane, a silane compound having a methoxy group or an ethoxy group is used; when the polymer is polyamide, at least one dicarboxylic acid component selected from dicarboxylic acids and their derivatives and a diamine component are used; When the polymer is a polyester, at least one dicarboxylic acid component selected from dicarboxylic acids and derivatives thereof and a diol component;

[0027] If the polymer is a polyurethane, an isocyanate and a compound containing a hydroxyl group; if the polymer is a polycarbonate, a bisphenol derivative and phosgene or a phosgene equivalent (e.g., trichlorophosgene) or diphenyl carbonate; When the polymer is a polyurea, it is a bisisocyanate derivative and a diamine component; when the polymer is a maleimide polymer, it is a maleimide derivative alone or copolymerized with styrene; In the case where the polymer is a polymer into which a compound having an isocyanuric acid skeleton or a triazine skeleton has been introduced, the compound has an isocyanuric acid skeleton or a triazine skeleton.

[0028] <Polyimide polymer> As the polymer contained in the liquid crystal aligning agent of the present invention, from the viewpoints of practicality as a liquid crystal aligning agent and mechanical and electrical properties of the coating film, one or more polymers selected from the group consisting of polyimide precursors and polyimides which are imidized products of polyimide precursors (hereinafter also referred to as polyimide-based polymers) are preferred. The polyimide polymer can be produced by a known method. For example, a polyamic acid, which is a polyimide precursor, is obtained by a polymerization (condensation) reaction of a tetracarboxylic acid component made of a tetracarboxylic dianhydride or a derivative thereof with a diamine component, and the polyimide is obtained by imidizing the polyimide precursor.

[0029] <Tetracarboxylic acid component> The polyamic acid, which is a polyimide precursor, may be, for example, one obtained from a tetracarboxylic acid component containing an aromatic, aliphatic, or alicyclic tetracarboxylic acid dianhydride. Here, the aromatic tetracarboxylic acid dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups, including at least one carboxyl group bonded to an aromatic ring. The aliphatic tetracarboxylic acid dianhydride is an acid dianhydride obtained by intramolecular dehydration of four carboxyl groups bonded to a chain hydrocarbon structure. However, it is not necessary for the polyamic acid dianhydride to be composed only of a chain hydrocarbon structure, and it may have an alicyclic structure or an aromatic ring structure as a part of it.

[0030] Alicyclic tetracarboxylic dianhydrides are acid dianhydrides obtained by intramolecular dehydration of four carboxyl groups, including at least one carboxyl group bonded to an alicyclic structure, but none of the four carboxyl groups are bonded to an aromatic ring. Furthermore, it is not necessary for the structure to be composed solely of an alicyclic structure, and it may also contain a chain hydrocarbon structure or an aromatic ring structure as part of it.

[0031] The polyamic acid of the present invention is preferably one obtained from a tetracarboxylic acid component containing a tetracarboxylic dianhydride represented by the following formula (2). [ka]

[0032] In the above formula (2), X is preferably a structure selected from the following (x-1) to (x-13). [ka]

[0033] In the above formulas (x-1) to (x-13), R 1 ~R 4each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an alkynyl group having 2 to 6 carbon atoms, a monovalent organic group having 1 to 6 carbon atoms and a fluorine atom, or a phenyl group. R 5 and R 6 Each of j and k independently represents an integer of 0 or 1. Each of A1 and A2 independently represents a single bond, -O-, -CO-, -COO-, phenylene, -SO2-, or -CONH-. Two A2 may be the same or different. *1 is a bond bonded to one acid anhydride group, and *2 is a bond bonded to the other acid anhydride group.)

[0034] The above formula (x-1) is preferably one selected from the group consisting of the following formulas (x1-1) to (x1-6). [ka] In the above formulae (x1-1) to (x1-6), *1 represents a bond bonded to one acid anhydride group, and *2 represents a bond bonded to the other acid anhydride group.

[0035] Preferred specific examples of the above formulae (x-12) and (x-13) include the following formulae (x-14) to (x-29), in which "*" indicates a bonding position. [ka] [ka] The amount of the tetracarboxylic dianhydride represented by the above formula (2) or a derivative thereof used is preferably 60 to 100 mol %, more preferably 80 to 100 mol %, and even more preferably 90 to 100 mol %, based on 1 mol of the total tetracarboxylic acid components to be reacted with the diamine components.

[0036] <Diamine component> The diamine component used in the production of the polyimide precursor is not particularly limited, but a diamine component containing a diamine represented by the following formula (3) is preferred. [ka]

[0037] In the above formula (3), A1 represents an alkylene group having 2 to 14 carbon atoms, or a group in which at least one of the -CH2- groups in the alkylene is replaced with -O-, -CO-, -OCO-, or -COO-, provided that the -CH2- groups are not consecutive. A1 is more preferably an alkylene group having 2 to 12 carbon atoms, or a group in which at least one of the -CH2- groups in the alkylene is replaced with -O-, -CO-, -OCO-, or -COO-, provided that the -CH2- groups are not consecutive, and even more preferably an alkylene group having 2 to 10 carbon atoms, or a group in which at least one of the -CH2- groups in the alkylene is replaced with -O-, -CO-, -OCO-, or -COO-, provided that the -CH2- groups are not consecutive. A2 represents a halogen atom, a hydroxyl group, an amino group, a thiol group, a nitro group, a phosphate group, or a monovalent organic group having 1 to 20 carbon atoms. When a2 is present in a plurality of instances, A2 may be the same or different. a is an integer of 0 to 4, and when a is present in a plurality of instances, a may be the same or different. b and c are each independently an integer of 1 or 2, and d is an integer of 0 or 1.

[0038] As the diamine represented by the above formula (3), diamines represented by the following formulas (3d-1) to (3d-9) are preferable. [ka] (In formulas (3d-8) and (3d-9), the two m's may be the same or different.)

[0039] As the diamine represented by the above formula (3), diamines represented by the following formulas (3-1) to (3-12) are more preferable. [ka]

[0040] The amount of the diamine represented by the above formula (3) used is preferably 60 to 100 mol %, more preferably 80 to 100 mol %, and even more preferably 90 to 100 mol %, per mol of the total diamine components to be reacted with the tetracarboxylic acid component.

[0041] The polyimide polymer used in the present invention may have at least one nitrogen-containing structure (hereinafter also referred to as nitrogen-containing structure) selected from the group consisting of a nitrogen-containing heterocycle (excluding the imide ring of polyimide), a secondary amino group, and a tertiary amino group, from the viewpoint of increasing the voltage retention rate of the resulting liquid crystal alignment film. The polyimide polymer having a nitrogen-containing structure can be obtained by using a monomer having a nitrogen-containing structure, for example, a diamine having a nitrogen-containing structure, as at least a part of the raw material.

[0042] Examples of the nitrogen-containing heterocycle include pyrrole, imidazole, pyrazole, triazole, pyridine, pyrimidine, pyridazine, pyrazine, indole, benzimidazole, purine, quinoline, isoquinoline, naphthyridine, quinoxaline, phthalazine, triazine, carbazole, acridine, piperidine, piperazine, pyrrolidine, hexamethyleneimine, etc. Among these, pyridine, pyrimidine, pyrazine, piperidine, piperazine, quinoline, carbazole, or acridine is preferred.

[0043] The secondary amino group and tertiary amino group that the diamine having a nitrogen-containing structure may have are represented, for example, by the following formula (n). [ka] In the above formula (n), R represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms. "*" represents a bond bonded to the hydrocarbon group. Examples of the monovalent hydrocarbon group R in the above formula (n) include alkyl groups such as methyl, ethyl, and propyl groups; cycloalkyl groups such as cyclohexyl groups; and aryl-containing groups such as phenyl and methylphenyl groups. R is preferably a hydrogen atom or a methyl group.

[0044] Specific examples of diamines having a nitrogen-containing structure include 2,6-diaminopyridine, 3,4-diaminopyridine, 2,4-diaminopyrimidine, 3,6-diaminocarbazole, N-methyl-3,6-diaminocarbazole, 1,4-bis-(4-aminophenyl)-piperazine, 3,6-diaminoacridine, N-ethyl-3,6-diaminocarbazole, N-phenyl-3,6-diaminocarbazole, N,N'-bis(4-aminophenyl)-benzidine, N,N'-bis(4-aminophenyl)-N,N'-dimethylbenzidine, 4,4'-diaminodiphenylamine, N,N-bis(4-aminophenyl)-methylamine, and compounds represented by the following formulae (z-1) to (z-18).

[0045] [ka] [ka]

[0046] From the viewpoint of increasing the voltage retention rate of the liquid crystal display element, the proportion of the diamine having a nitrogen-containing structure used is preferably 1 mol % or more, more preferably 2 mol % or more, based on the total amount of the diamine used in the synthesis, and the proportion is preferably 90 mol % or less, more preferably 80 mol % or less.

[0047] The polyimide polymer used in the present invention may contain other diamines in addition to the diamines described above. Examples of other diamines are given below, but the present invention is not limited to these. 4-(2-(methylamino)ethyl)aniline, 4-(2-aminoethyl)aniline, 4,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylether, diamines having a photoalignment group such as diamines represented by the following formulas (g-1) to (g-9), 1-(4-aminophenyl)-1,3,3-trimethyl-1H-indan-5-amine, 1-(4-aminophenyl)-2,3-dihydro ... H-inden-6-amine, carboxyl group-containing diamines such as 3,5-diaminobenzoic acid, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, bis[4-(4-aminophenoxy)phenyl]ether, 4,4'-bis(4-aminophenoxy)biphenyl, 1,4-diaminonaphthalene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,7-diaminonaphthalene, 2,2'-bis[4-(4-aminophenoxy)phenyl]ether, photocatalysts such as 2,4-diamino-N,N-diallylaniline, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2'-bis(4-aminophenyl)propane, diamines having a urea bond such as diamines represented by the following formulas (u-1) to (u-3), diamines having an amide bond such as diamines represented by the following formulas (u-4) to (u-7), 2-(2,4-diaminophenoxy)ethyl methacrylate, and 2,4-diamino-N,N-diallylaniline diamines having a polymerizable group at the end, diamines having a steroid skeleton such as cholestanyloxy-3,5-diaminobenzene, cholestenyloxy-3,5-diaminobenzene, cholestanyloxy-2,4-diaminobenzene, cholestanyl 3,5-diaminobenzoate, cholestanyl 3,5-diaminobenzoate, lanostannyl 3,5-diaminobenzoate, and 3,6-bis(4-aminobenzoyloxy)cholestane; diamines represented by the following formulae (V-1) to (V-6),

[0048] [ka]

[0049] [ka] (In formula (u-7), the two m's may be the same or different.)

[0050] [ka] (In formula (v-6), the two k's may be the same or different.)

[0051] (In the above formulas (V-1) to (V-6), X v1 ~X v4 , X p1 ~X p2 are each independently -(CH2) a -(a is an integer of 1 to 15), -CONH-, -NHCO-, -CON(CH3)-, -NH-, -O-, -CHO-, -CHOCO-, -COO-, or -OCO-; v5 represents -O-, -CH2O-, -CH2OCO-, -COO-, or -OCO-. Xa represents a single bond, -O-, -NH-, -O-(CH2) m -O-, -C(CH3)2-, -CO-, -(CH2) m -, -SO2-, -OC(CH3)2-, -CO-(CH2) m -, -NH-(CH2) m -, -SO2-(CH2) m -, -CONH-(CH2) m -, -CONH-(CH2) m -NHCO-, -COO-(CH2) m -OCO-, -CONH-, -NH-(CH2) m -NH- or -SO2-(CH2) m represents -SO2-; m is an integer from 1 to 8. v1 ~R v4 , R 1a ~R 1beach independently represents an alkyl group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or an alkoxyalkyl group having 2 to 20 carbon atoms. diamines having a group "-N(D)-" (D represents a protecting group which is eliminated by heating and is replaced with a hydrogen atom, preferably a tert-butoxycarbonyl group) such as those of the following formulas (5-1) to (5-11); diamines having an oxazoline structure such as those of the following formulas (Ox-1) to (Ox-2); diamines having a radical polymerization initiator function such as 1-(4-(2,4-diaminophenoxy)ethoxy)phenyl)-2-hydroxy-2-methylpropanone, 2-(4-(2-hydroxy-2-methylpropanoyl)phenoxy)ethyl-3,5-diaminobenzoate, 4,4-diaminobenzophenone, and 3,4'-diaminobenzophenone.

[0052] [ka] (Boc represents a t-butoxycarbonyl group.)

[0053] [ka]

[0054] <Method of producing polyamic acid> The polyamic acid, which is a polyimide precursor used in the present invention, can be produced by the following method. Specifically, it can be synthesized by reacting the above-mentioned tetracarboxylic acid component and the above-mentioned diamine component in the presence of an organic solvent at −20 to 150° C., preferably 0 to 50° C., for 30 minutes to 24 hours, preferably 1 to 12 hours (polycondensation). The organic solvent used in the above reaction is preferably N,N-dimethylformamide, N-methyl-2-pyrrolidone, or γ-butyrolactone in terms of the solubility of the monomer and polymer, and two or more of these may be mixed for use. The concentration of the polymer is preferably 1 to 30% by mass, more preferably 5 to 20% by mass, from the viewpoints that the polymer is less likely to precipitate and a high molecular weight product is easily obtained.

[0055] The polyamic acid obtained by the above reaction can be precipitated and collected by injecting the reaction solution into a poor solvent while thoroughly stirring it. In addition, the precipitation can be carried out several times, washed with a poor solvent, and then dried at room temperature or by heating to obtain a purified polyamic acid powder. The poor solvent is not particularly limited, but examples thereof include water, methanol, ethanol, hexane, butyl cellosolve, acetone, and toluene.

[0056] When the polyimide precursor is a polyamic acid ester, it can be produced by known methods such as (1) a method of esterifying a polyamic acid obtained from a tetracarboxylic dianhydride and a diamine, (2) a method of reacting a tetracarboxylic diester dichloride with a diamine, or (3) a method of polycondensing a tetracarboxylic diester with a diamine.

[0057] The polyimide precursor may be a terminal-capped polymer obtained by using an appropriate terminal-capping agent together with the above-mentioned tetracarboxylic acid derivative and diamine during the production thereof. Examples of the end-capping agent include acid monoanhydrides such as maleic anhydride, nadic anhydride, phthalic anhydride, itaconic anhydride, cyclohexanedicarboxylic anhydride, 3-hydroxyphthalic anhydride, and trimellitic anhydride, di-tert-butyl dicarbonate, monoamine compounds such as aniline, 2-aminophenol, 3-aminophenol, 4-aminosalicylic acid, 5-aminosalicylic acid, 6-aminosalicylic acid, 2-aminobenzoic acid, 3-aminobenzoic acid, and 4-aminobenzoic acid, and monoisocyanate compounds such as ethyl isocyanate, phenyl isocyanate, and naphthyl isocyanate. The proportion of the end-capping agent used is preferably 40 parts by mol or less, and more preferably 30 parts by mol or less, per 100 parts by mol of the total of the diamine components used.

[0058] <Polyimide manufacturing method> The polyimide used in the present invention can be produced by imidizing a polyimide precursor, a polyamic acid or a polyamic acid ester, by a known method. For example, when producing a polyimide from a polyamic acid, it is convenient to carry out (chemical) imidization by adding a catalyst to a solution of a polyamic acid obtained by reacting a diamine component with a tetracarboxylic acid component. The imidization can be carried out by stirring the polymer to be imidized in an organic solvent in the presence of a basic catalyst and an acid anhydride.

[0059] As the organic solvent, the solvent used in the polymerization reaction described above can be used. As the basic catalyst, pyridine, triethylamine, trimethylamine, tributylamine, trioctylamine, etc. can be mentioned. Among them, pyridine is preferable because it has a suitable basicity for proceeding with the reaction. In addition, as the acid anhydride, acetic anhydride, trimellitic anhydride, pyromellitic anhydride, etc. can be mentioned. Among them, acetic anhydride is preferable because it is easy to purify after the reaction is completed.

[0060] The temperature during the imidization reaction is -20 to 140°C, preferably 0 to 100°C, and the reaction time is 1 to 100 hours. The amount of the basic catalyst is 0.5 to 30 times by mole, preferably 2 to 20 times by mole, the amic acid group, and the amount of the acid anhydride is 1 to 50 times by mole, preferably 3 to 30 times by mole, the amic acid group. The imidization rate of the resulting polymer can be controlled by adjusting the amount of the catalyst, temperature, and reaction time. The imidization ratio in this specification refers to the ratio of imide groups to the total amount of imide groups derived from tetracarboxylic dianhydride or its derivatives and carboxyl groups (or its derivatives). In polyimides, the imidization ratio does not necessarily need to be 100%, and can be adjusted as desired depending on the application or purpose. The imidization ratio of the polyimide used in the present invention is preferably 20 to 100%, more preferably 50 to 99%.

[0061] The polyimide solution obtained as described above can be poured into a poor solvent while stirring to precipitate the polymer. The precipitation is carried out several times, washed with a poor solvent, and then dried at room temperature or by heating to obtain a purified polyimide powder. The poor solvent is not particularly limited, but examples thereof include methanol, acetone, hexane, butyl cellosolve, heptane, methyl ethyl ketone, methyl isobutyl ketone, ethanol, toluene, and benzene.

[0062] The molecular weight of the polyimide precursor and polyimide produced as described above is preferably a weight average molecular weight of 2,000 to 500,000, more preferably 5,000 to 300,000, and even more preferably 10,000 to 100,000. The number average molecular weight is preferably 1,000 to 250,000, more preferably 2,500 to 150,000, and even more preferably 5,000 to 50,000.

[0063] <Liquid crystal alignment agent> The liquid crystal aligning agent of the present invention has a form in which the aromatic compound of the above formula (1) is added to a solution in which a polymer capable of aligning liquid crystals is dissolved in a solvent. The content (concentration) of the polymer contained in the liquid crystal alignment agent of the present invention can be appropriately changed depending on the thickness of the coating film to be formed, but it is preferably 1% by mass or more from the viewpoint of forming a uniform and defect-free coating film, and is preferably 10% by mass or less from the viewpoint of storage stability of the solution. The content (concentration) of the aromatic compound of the above formula (1) added to the liquid crystal aligning agent of the present invention is preferably 0.1 to 5 mass%, more preferably 0.15 to 5 mass%, and particularly preferably 0.2 to 5 mass%. In addition, the content of the aromatic compound of the above formula (1) is preferably 1 to 15 mass %, more preferably 2 to 10 mass %, and particularly preferably 2 to 8 mass %, as the total content of the polymer and the aromatic compound of the above formula (1) contained in the liquid crystal alignment agent.

[0064] The solvent used in the liquid crystal aligning agent of the present invention is not particularly limited as long as it is a solvent that dissolves the aromatic compound of the above formula (1) and the above polymer. Specific examples are given below. For example, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, dimethylsulfoxide, γ-butyrolactone, 1,3-dimethyl-2-imidazolidinone, methyl ethyl ketone, cyclohexanone, cyclopentanone, 3-methoxy-N,N-dimethylpropanamide, 4-hydroxy-4-methyl-2-pentanone, and solvents represented by the following formulae [D-1] to [D-3] can be mentioned.

[0065] [ka] (In formula [D-1], D 1 represents an alkyl group having 1 to 3 carbon atoms, and in formula [D-2], D 2 represents an alkyl group having 1 to 3 carbon atoms, and in formula [D-3], D 3 represents an alkyl group having 1 to 4 carbon atoms). Of these, the solvent in the present invention is preferably N-methyl-2-pyrrolidone, N-ethyl-2-pyrrolidone, γ-butyrolactone, 3-methoxy-N,N-dimethylpropanamide, or 1,3-dimethyl-2-imidazolidinone (hereinafter, these are also referred to as good solvents).

[0066] The liquid crystal aligning agent of the present invention may contain a solvent (also called a poor solvent) that improves the coating property and surface smoothness of the liquid crystal alignment film when the liquid crystal aligning agent is applied. The poor solvent is preferably 1 to 80 mass % of the total solvent contained in the liquid crystal aligning agent. Of these, 10 to 80 mass % is preferable. More preferably, 20 to 70 mass %.

[0067] Specific examples of poor solvents are given below: ethanol, isopropyl alcohol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, isopentyl alcohol, tert-pentyl alcohol, 3-methyl-2-butanol, neopentyl alcohol, 1-hexanol, 2-methyl-1-pentanol, 2-methyl-2-pentanol, 2-ethyl-1-butanol, 1-heptanol, 2-heptanol, 3-heptanol, 1-octanol, 2-octanol, and 2-octanol. hexanediol, 2-ethyl-1-hexanol, cyclohexanol, 1-methylcyclohexanol, 2-methylcyclohexanol, 3-methylcyclohexanol, 1,2-ethanediol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 2-methyl-2,4-pentanediol, 2-ethyl-1,3-hexanediol, dipropyl ether, dibutyl ether, dihexyl ether, dioxane ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, 1,2-butoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, diethylene glycol dibutyl ether, 2-pentanone, 3-pentanone, 2-hexanone, 2-heptanone, 4-heptanone, 3-ethoxybutyl acetate, 1-methylpentyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, Ethylene glycol monoacetate, ethylene glycol diacetate, propylene carbonate, ethylene carbonate, 2-(methoxymethoxy)ethanol, butyl cellosolve, ethylene glycol monoisoamyl ether, ethylene glycol monohexyl ether, 2-(hexyloxy)ethanol, furfuryl alcohol, diethylene glycol, propylene glycol, 1-butoxy-2-propanol, 1-(butoxyethoxy)propanol, propylene glycol monomethyl ether acetate, dipropylene glycol,Dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, butyl cellosolve acetate, ethylene glycol monoacetate, ethylene glycol diacetate, diethylene glycol monoethyl ether acetate, diacetone alcohol, propylene glycol diacetate, diisopentyl ether, diethylene glycol monobutyl ether acetate, 2-(2-ethoxyethoxy)ethyl acetate, diethylene glycol acetate, tri Examples of the solvent include ethylene glycol, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, n-butyl acetate, propylene glycol monoethyl ether acetate, methyl pyruvate, ethyl pyruvate, methyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-methoxypropionate, 3-ethoxypropionic acid, 3-methoxypropionic acid, propyl 3-methoxypropionate, butyl 3-methoxypropionate, n-propyl lactate, n-butyl lactate, isoamyl lactate, diisobutyl ketone, ethyl carbitol, and the solvents represented by the above formulae [D-1] to [D-3]. Of these, it is preferable to use butyl cellosolve, 1-butoxy-2-propanol, butyl cellosolve acetate, dipropylene glycol monomethyl ether, diacetone alcohol, diethylene glycol diethyl ether, diisopentyl ether, propylene glycol diacetate, diisobutyl ketone, ethyl carbitol, or dipropylene glycol dimethyl ether.

[0068] The liquid crystal aligning agent of the present invention may contain a crosslinkable compound having an epoxy group, an isocyanate group, an oxetanyl group or a cyclocarbonate group, a crosslinkable compound having at least one substituent selected from the group consisting of a hydroxy group, a hydroxyalkyl group and a lower alkoxyalkyl group, or a crosslinkable compound having a polymerizable unsaturated bond (excluding the aromatic compound of formula (1)). It is preferable that the crosslinkable compound has two or more of these substituents or polymerizable unsaturated bonds. Two or more types of crosslinkable compounds may be combined. Specific examples of preferred crosslinkable compounds include compounds represented by the following formulas (CL-1) to (CL-11). [ka] The content of the crosslinkable compound in the liquid crystal aligning agent of the present invention is preferably from 0.1 to 150 parts by mass, more preferably from 0.1 to 100 parts by mass, based on 100 parts by mass of all the polymers.

[0069] The liquid crystal aligning agent of the present invention may contain a compound that improves the uniformity of the thickness and the surface smoothness of the film-like material obtained by applying the agent. Examples of such compounds include fluorine-based surfactants, silicone-based surfactants, nonionic surfactants, etc. More specific examples include F-TOP EF301, EF303, EF352 (all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Megafac F171, F173, R-30 (all manufactured by DIC Corporation), Fluorad FC430, FC431 (all manufactured by 3M), Asahiguard AG710, Surflon S-382, SC101, SC102, SC103, SC104, SC105, SC106 (all manufactured by AGC Corporation), etc.

[0070] Furthermore, the liquid crystal alignment agent may contain nitrogen-containing heterocyclic amines represented by formulae [M1] to [M156], which are listed in International Publication WO2011 / 132751 (published on October 27, 2011)

[0194] to

[0200] , as compounds that promote charge transfer in the liquid crystal alignment film and promote charge escape from the element. This amine may be added directly to the liquid crystal alignment agent, but it is preferable to add it after making it into a solution with a concentration of 0.1 to 10% by mass, preferably 1 to 7% by mass. This solvent is not particularly limited as long as it dissolves the specific polymer.

[0071] <Liquid crystal alignment film / Liquid crystal display element> The liquid crystal alignment film of the present invention is a film obtained by applying the above liquid crystal alignment agent to a substrate, drying and baking. The substrate is not particularly limited as long as it is a highly transparent substrate, and examples thereof include glass substrates, silicon nitride substrates, and plastic substrates such as acrylic substrates and polycarbonate substrates. Substrates on which ITO electrodes for driving liquid crystals are formed are preferred from the viewpoint of process simplification. In a reflective liquid crystal display element, an opaque material such as a silicon wafer can be used for only one substrate, and in this case, a light-reflecting material such as aluminum can be used for the electrode.

[0072] Examples of the method for applying the liquid crystal alignment agent to a substrate and forming a film include screen printing, offset printing, flexographic printing, an inkjet method, a spray method, etc. Among these, the application and film formation method by the inkjet method is preferably used. After the liquid crystal alignment agent is applied onto the substrate, the solvent can be evaporated to form a film-like material (coating) by a heating means such as a hot plate, a heat circulation type oven, or an IR (infrared) type oven. The temperature and time for the drying and baking process after the application of the liquid crystal alignment agent can be selected arbitrarily. Usually, the material is baked at 50 to 180°C for 1 to 10 minutes to sufficiently remove the contained solvent, or may be baked at 150 to 300°C for 5 to 120 minutes to further perform thermal imidization. If the film-like material after baking is too thin, the reliability of the liquid crystal display element may decrease, so the thickness is preferably 5 to 300 nm, more preferably 10 to 200 nm.

[0073] The alignment treatment method for the liquid crystal alignment film obtained from the liquid crystal aligning agent of the present invention may be a rubbing treatment method, but a photo-alignment treatment method is preferred. As the photo-alignment treatment method, a method in which the surface of the film-like material is irradiated with radiation deflected in a certain direction, and optionally baked at a temperature of preferably 150 to 250°C to impart liquid crystal alignment properties (also called liquid crystal alignment ability) can be mentioned. As the radiation, ultraviolet rays or visible light having a wavelength of 100 to 800 nm can be used. Among them, ultraviolet rays having a wavelength of 100 to 400 nm are preferred, and more preferably 200 to 400 nm are preferred.

[0074] In the case of irradiating with radiation, in order to improve the liquid crystal alignment, the substrate having the film-like material may be irradiated while being heated at 50 to 250° C. The radiation dose is 1 to 10,000 mJ / cm 2 . 2 Among them, 100 to 5,000 mJ / cm is preferable. 2 The liquid crystal alignment film thus produced is capable of stably aligning liquid crystal molecules in a certain direction. Furthermore, the liquid crystal alignment film irradiated with polarized radiation by the above method can be treated with water or a solvent, or the liquid crystal alignment film irradiated with radiation can be heat-treated.

[0075] The solvent used in the contact treatment is not particularly limited as long as it dissolves the decomposition product generated from the film-like material by irradiation with radiation. Specific examples include water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, 1-methoxy-2-propanol, 1-methoxy-2-propanol acetate, butyl cellosolve, ethyl lactate, methyl lactate, diacetone alcohol, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, propyl acetate, butyl acetate, cyclohexyl acetate, and the like. Among these, water, 2-propanol, 1-methoxy-2-propanol, or ethyl lactate is preferred from the viewpoint of versatility and solvent safety. Water, 1-methoxy-2-propanol, or ethyl lactate is more preferred. The solvent may be one type or a combination of two or more types.

[0076] The contact treatment includes immersion treatment and spray treatment (also called spray treatment). The treatment time in these treatments is preferably 10 seconds to 1 hour from the viewpoint of efficiently dissolving the decomposition products generated from the film-like material by irradiation with radiation. In particular, immersion treatment for 1 to 30 minutes is preferred. The solvent during the contact treatment may be at room temperature or heated, preferably 10 to 80°C. In particular, 20 to 50°C is preferred. In addition, from the viewpoint of the solubility of the decomposition products, ultrasonic treatment or the like may be performed as necessary.

[0077] After the contact treatment, it is preferable to perform rinsing (also called rinsing) with a low boiling point solvent such as water, methanol, ethanol, 2-propanol, acetone, methyl ethyl ketone, etc., and calcination. In this case, either rinsing or calcination may be performed, or both may be performed. The calcination temperature is preferably 150 to 300°C. Of these, 180 to 250°C is preferable, and 200 to 230°C is more preferable. The calcination time is preferably 10 seconds to 30 minutes, and of these, 1 to 10 minutes is preferable. The heat treatment of the coating film irradiated with the above-mentioned radiation is more preferably carried out at 50 to 300° C. for 1 to 30 minutes, and even more preferably at 120 to 250° C. for 1 to 30 minutes.

[0078] The liquid crystal alignment film of the present invention is suitable as a liquid crystal alignment film for a horizontal electric field type liquid crystal display element such as an IPS type or an FFS type, from the viewpoint of obtaining high liquid crystal alignment properties, and is particularly useful as a liquid crystal alignment film for an FFS type liquid crystal display element. The liquid crystal display element is obtained by obtaining a substrate with a liquid crystal alignment film obtained from the liquid crystal alignment agent of the present invention, and then producing a liquid crystal cell by a known method, and using the liquid crystal cell. As an example of a method for fabricating a liquid crystal cell, a liquid crystal display element having a passive matrix structure will be described below. However, a liquid crystal display element having an active matrix structure in which a switching element such as a TFT (Thin Film Transistor) is provided in each pixel portion constituting an image display may also be used.

[0079] Specifically, transparent glass substrates are prepared, and a common electrode is provided on one substrate, and a segment electrode is provided on the other substrate. These electrodes may be, for example, ITO electrodes, and are patterned to display a desired image. Next, an insulating film is provided on each substrate so as to cover the common electrode and the segment electrode. The insulating film may be, for example, a SiO2-TiO2 film formed by the sol-gel method.

[0080] Next, a liquid crystal alignment film is formed on each substrate, and one substrate is superimposed on the other substrate so that the liquid crystal alignment film faces each other, and the periphery is bonded with a sealant. In order to control the gap between the substrates, a spacer is usually mixed into the sealant, and it is also preferable to scatter spacers for controlling the gap between the substrates on the inner surface where the sealant is not provided. An opening is provided in a part of the sealant so that liquid crystal can be filled from the outside. Next, a liquid crystal material is injected into the space surrounded by the two substrates and the sealant through the opening provided in the sealant, and then this opening is sealed with an adhesive. For the injection, a vacuum injection method or a method utilizing capillary action in the atmosphere may be used. The liquid crystal material may be either a positive type liquid crystal material or a negative type liquid crystal material, but a negative type liquid crystal material is preferable. Next, a polarizing plate is installed. Specifically, a pair of polarizing plates is attached to the surface opposite to the liquid crystal layer of the two substrates. EXAMPLES

[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. The abbreviations of compounds and the methods for measuring the properties are as follows. <Solvent> DMF: N,N-dimethylformamide, NMP: N-methyl-2-pyrrolidone GBL: γ-butyrolactone, BCS: butyl cellosolve <Diamine> DA-1: 1,2-bis(4-aminophenoxy)ethane DA-2: N-tert-butoxycarbonyl-N-(2-(4-aminophenyl)ethyl)-N-(4-aminobenzyl)amine DA-3: p-phenylenediamine, DA-4: See formula (DA-4) below DA-5: 4,4'-diaminodiphenylamine DA-6: 4,4'-diaminodiphenylmethane

[0082] [ka]

[0083] <Tetracarboxylic acid dianhydride> [ka]

[0084] <Additives> [ka]

[0085] T-1 to T-4 are novel compounds not yet disclosed in the literature, and their synthesis methods are described in detail in the following Synthesis Examples 1 to 4.

[0086] < 1 H-NMR Measurement Equipment: Fourier transform superconducting nuclear magnetic resonance spectrometer (FT-NMR) "AVANCE III" (BRUKER) 500MHz. Solvent: deuterated chloroform (CDCl3) or deuterated N,N-dimethylsulfoxide ([D6]-DMSO). Standard: tetramethylsilane (TMS).

[0087] (Synthesis Example 1) Synthesis of [T-1]: [ka]

[0088] In a 1L four-neck flask, 4,4'-biphenyldiboronic acid (22.5g, 93mmol), 3-chloro-2-methyl-1-propene (95.1g, 1050mmol), Najera catalyst I (0.244g, 0.3mmol), tetrabutylammonium bromide (13.5g, 42mmol), potassium carbonate (116.1g, 840mmol), DMF (250g), and pure water (13g) were charged and stirred at 130°C. After the reaction was completed, the reaction solution was poured into ethyl acetate (1000g), neutralized with 1N hydrochloric acid aqueous solution (1000g), and washed with pure water (1000g). The obtained organic layer was concentrated, and the obtained crude product was isolated by silica gel column chromatography (eluent: hexane only) to obtain 4.7g of a white solid. The following 1 The results of H-NMR confirmed that this solid was [T-1]. 1 H-NMR(500MHz,[D6]-DMSO):δ7.57-7.60(d,4H),7.25-7.27(d,4H),4.80-4.81(m,2H),4.76-4.77(m,2H),3.34(s,4H),1.65(s,6H)

[0089] (Synthesis Example 2) Synthesis of [T-2]: [ka]

[0090] In a 1L four-neck flask, 2,6-dimethylphenol (50.0 g, 409 mmol), 3-chloro-2-methyl-1-propene (37.0 g, 409 mmol), potassium carbonate (84.8 g, 613 mmol), potassium iodide (6.80 g, 41 mmol), and DMF (500 g) were charged and stirred at 80°C. After the reaction was completed, the reaction system was poured into ethyl acetate (500 g), and the organic layer was washed with pure water (1500 g). The obtained organic layer was concentrated, and the obtained crude product was isolated by silica gel column chromatography (eluent: hexane only), to obtain 66.6 g of [T-2-1].

[0091] [T-2-1] (66.6 g, 378 mmol) and N,N-dimethylaniline (300 g) were charged into a 1 L four-neck flask and stirred at 180° C. After completion of the reaction, the reaction system was poured into ethyl acetate (1000 g), and the organic layer was washed with 1N hydrochloric acid aqueous solution (1000 g) and then with pure water (1000 g), and the organic layer was concentrated to obtain 66.6 g of [T-2-2].

[0092] [T-2-2] (17.3 g, 98 mmol), 1,2-bis(tosyloxy)ethane (18.5 g, 50 mmol), potassium carbonate (20.7 g, 150 mmol), and DMF (170 g) were charged into a 500 mL four-neck flask and stirred at 80°C. After completion of the reaction, the reaction system was poured into ethyl acetate (500 g), and the organic layer was washed with pure water (1000 g). The obtained organic layer was concentrated, and the crude product was isolated by silica gel column chromatography (eluent: ethyl acetate / hexane = 1 / 30 (volume ratio)), yielding 10.0 g of a transparent liquid. The reaction mixture shown below was 1 The H-NMR results confirmed that this liquid was [T-2]. 1 H-NMR (500MHz, CDCl3): δ6.83(s,4H),4.78-4.79(m,2H),4.72-4.73(m,2H),4.09(s,4H),3.20(s,4H),2.30(s,12H),1.67(s,6H)

[0093] (Synthesis Example 3) Synthesis of [T-3]: [ka]

[0094] 4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenol (18.9 g, 86 mmol), 1,2-bis(tosyloxy)ethane (15.9 g, 43 mmol), potassium carbonate (17.8 g, 129 mmol), and DMF (190 g) were charged into a 500 mL four-neck flask and stirred at 80 ° C. After the reaction was completed, the reaction system was filtered to remove potassium carbonate, the filtrate was poured into ethyl acetate (1000 g), and the organic layer was washed with pure water (2000 g). The obtained organic layer was concentrated, ethanol (60 g) was added to the crude product, and repulp washing was performed at room temperature to obtain 14.0 g of [T-3-1].

[0095] A 500 mL four-neck flask was charged with [T-3-1] (13.5 g, 29 mmol), 3-chloro-2-methyl-1-propene (39.4 g, 435 mmol), Najera catalyst I (0.071 g, 0.09 mmol), tetrabutylammonium bromide (3.73 g, 12 mmol), potassium carbonate (32.1 g, 232 mmol), DMF (100 g), and pure water (25 g), and the mixture was stirred at 130 °C.

[0096] After the reaction was completed, the reaction solution was poured into ethyl acetate (600 g) and washed with pure water (1200 g). The obtained organic layer was concentrated, and the crude product was isolated by silica gel column chromatography (eluent: ethyl acetate / hexane = 1 / 30 (volume ratio)) to obtain 1.6 g of a white solid. 1 The results of H-NMR confirmed that this solid was the desired [T-3]. 1 H-NMR (500MHz, CDCl3): δ7.09-7.11(d,4H),6.87-6.89(d,4H),4.78-4.79(m,2H),4.70-4.71(m,2H),4.30(s,4H),3.26(s,4H),1.67(s,6H)

[0097] (Synthesis Example 4) Synthesis of [T-4]: [ka]

[0098] 2,6-Dimethylphenol (25.0 g, 205 mmol), allyl bromide (29.8 g, 246 mmol), potassium carbonate (42.5 g, 308 mmol), and DMF (250 g) were charged into a 500 mL four-neck flask and stirred at 80° C. After completion of the reaction, the reaction system was poured into ethyl acetate (300 g), and the organic layer was washed with pure water (600 g) and concentrated to obtain 30.8 g of [T-4-1].

[0099] [T-4-1] (30.8 g, 190 mmol) and N,N-dimethylaniline (200 g) were charged into a 500 mL four-neck flask and stirred at 180° C. After completion of the reaction, the reaction system was poured into ethyl acetate (500 g), and the organic layer was washed with 1N hydrochloric acid aqueous solution (500 g) and pure water (500 g), and the organic layer was concentrated to obtain 30.3 g of [T-4-2].

[0100] [T-4-2] (30.3 g, 187 mmol), 1,2-bis(tosyloxy)ethane (34.4 g, 93 mmol), potassium carbonate (38.6 g, 279 mmol), and DMF (360 g) were charged into a 500 mL four-neck flask and stirred at 80°C. After completion of the reaction, the reaction system was poured into ethyl acetate (1000 g), and the organic layer was washed with pure water (2000 g). The obtained organic layer was concentrated, and the crude product was isolated by silica gel column chromatography (eluent: ethyl acetate / hexane = 1 / 80 (volume ratio)), yielding 18.7 g of a transparent liquid. The reaction mixture shown below was 1 The results of H-NMR confirmed that this liquid was the desired [T-4]. 1 H-NMR(500MHz,[D6]-DMSO):δ7.02(s,4H),5.87-5.96(m,2H),5.05-5.09(m,2H),5.00-5.03(m,2H),4.04(s,4H),3.24-3.25(d,4H),2.22(s,12H)

[0101] <Method of measuring viscosity> Measurements were performed using an E-type viscometer TVE-22H (manufactured by Toki Sangyo Co., Ltd.) with a sample volume of 1.1 mL, a cone rotor TE-1 (1°34', R24), and a temperature of 25°C.

[0102] <Method of measuring molecular weight> The measurements were performed using a GPC (room temperature gel permeation chromatography) device, and the number average molecular weight (Mn) and weight average molecular weight (Mw) were calculated as values ​​calculated for polyethylene glycol and polyethylene oxide. GPC apparatus: Shodex (GPC-101), column: Shodex (KD803, KD805 in series), column temperature: 50°C, eluent: N,N-dimethylformamide (additives: lithium bromide hydrate (LiBr·H2O) 30mmol / L, phosphoric acid anhydrous crystal (o-phosphoric acid) 30mmol / L, tetrahydrofuran (THF) 10ml / L), flow rate: 1.0ml / min Standard samples for creating a calibration curve: TSK standard polyethylene oxide manufactured by Tosoh Corporation (weight average molecular weight (Mw) approximately 900,000, 150,000, 100,000, 30,000), and polyethylene glycol manufactured by Polymer Laboratory Co., Ltd. (peak top molecular weight (Mp) approximately 12,000, 4,000, 1,000). In order to avoid overlapping peaks, measurements were performed separately on two samples: a sample made by mixing four types of 900,000, 100,000, 12,000, and 1,000, and a sample made by mixing three types of 150,000, 30,000, and 4,000.

[0103] <Method for measuring imidization rate> 20 mg of polyimide powder was placed in an NMR sample tube (NMR sampling tube standard, φ5 (Kusano Scientific Co., Ltd.)), deuterated dimethyl sulfoxide (DMSO-d6, 0.05% TMS (tetramethylsilane) mixture) (0.53 mL) was added, and the mixture was sonicated to completely dissolve. This solution was measured by proton NMR at 500 MHz using a Fourier transform superconducting nuclear magnetic resonance (FT-NMR) "AVANCE III" (BRUKER Co., Ltd.). The imidization rate was calculated by the following formula using the proton peak integrated value of this proton and the proton peak integrated value of the proton peak derived from the NH group of the amic acid that appears around 9.5 ppm to 10.0 ppm. Imidization rate (%) = (1-α·x / y) × 100 In the above formula, x is the integrated value of the proton peak derived from the NH group of the amic acid, y is the integrated value of the peak of the reference proton, and α is the ratio of the number of reference protons to one NH group proton of the amic acid in the case of polyamic acid (imidization rate 0%).

[0104] (Synthesis Example 5) DA-1 (3.91g, 16.0mmol), DA-2 (2.19g, 6.41mmol), DA-3 (0.519g, 4.80mmol), and DA-4 (1.54g, 4.81mmol) were weighed into a 100mL four-neck flask equipped with a stirrer and a nitrogen inlet tube, and NMP (46.2g) was added. The mixture was stirred and dissolved while nitrogen was supplied. CA-1 (5.70g, 25.4mmol) and CA-2 (1.20g, 4.80mmol) were added to this diamine solution while stirring, and NMP (39.1g) was added so that the solid concentration became 15% by mass. The mixture was stirred at 40°C for 24 hours to obtain polyamic acid solution (A) (viscosity: 450mPa·s). The molecular weight of the polyamic acid was Mn=11,200, Mw=26,900.

[0105] (Synthesis Example 6) DA-5 (5.10g, 25.6mmol) and DA-6 (1.27g, 6.41mmol) were placed in a 100mL four-neck flask equipped with a stirrer and nitrogen inlet tube, and NMP (36.1g) was added. The mixture was stirred and dissolved while nitrogen was supplied. CA-2 (4.00g, 16.0mmol) and CA-3 (4.42g, 15.0mmol) were added to this diamine solution while stirring, and NMP (47.7g) was added so that the solid concentration became 15% by mass. The mixture was stirred at 50°C for 24 hours to obtain polyamic acid solution (B) (viscosity: 904mPa·s). The molecular weight of the polyamic acid was Mn=14,600, Mw=37,500.

[0106] (Synthesis Example 7) The obtained polyamic acid solution (A) (30 g) was weighed out into a 100 ml four-neck flask equipped with a stirrer and a nitrogen inlet tube, and NMP (15.0 g) was added and stirred for 30 minutes. Acetic anhydride (4.89 g) and pyridine (1.51 g) were added to the obtained polyamic acid solution, and the mixture was heated at 50°C for 2 hours and 30 minutes to perform chemical imidization. The obtained reaction solution was poured into methanol (154 mL) while stirring, and the precipitate was collected by filtration, and then washed three times with methanol (154 mL). The obtained resin powder was dried at 60°C for 12 hours to obtain polyimide resin powder (A). The imidization rate of this polyimide resin powder was 64%, Mn = 9,900, and Mw = 20,000.

[0107] (Synthesis Example 8) The polyimide resin powder (A) (3.00 g) obtained in Synthesis Example 7 was weighed out into a 100 mL Erlenmeyer flask, and NMP (22.0 g) was added so that the solid concentration became 12%, and the mixture was stirred at 70° C. for 24 hours to dissolve the polyimide resin powder (A), thereby obtaining a polyimide solution (A).

[0108] Example 1 The polyimide solution (A) (3.80 g) obtained in Synthesis Example 8 and the polyamic acid solution (B) (4.56 g) obtained in Synthesis Example 6 were weighed into a 100 mL Erlenmeyer flask, T-1 (0.114 g), NMP (1.64 g), GBL (6.00 g), and BCS (4.00 g) were added, and the mixture was stirred at room temperature for 3 hours to obtain a liquid crystal alignment agent (1). No abnormalities such as turbidity or precipitation were observed in this liquid crystal alignment agent, and it was confirmed that the solution was homogeneous.

[0109] (Examples 2 to 5) The liquid crystal alignment agents (2) to (5) of Examples 2 to 5 were obtained in the same manner as in Example 1, except that T-2, T-3, T-4, or T-5 was used instead of T-1. It was confirmed that the liquid crystal alignment agents (2) to (5) were homogeneous solutions without any abnormality such as turbidity or precipitation.

[0110] Comparative Example 1 The polyimide solution (A) (3.80 g) obtained in Synthesis Example 8 and the polyamic acid solution (B) (4.56 g) obtained in Synthesis Example 6 were weighed into a 100 mL Erlenmeyer flask, and NMP (1.64 g), GBL (6.00 g), and BCS (4.00 g) were added and stirred at room temperature for 3 hours to obtain a liquid crystal alignment agent (6).

[0111] Comparative Example 2 A liquid crystal aligning agent (7) was obtained in the same manner as in Example 1, except that T-6 was used instead of T-1. In addition, the liquid crystal alignment agents (6) and (7) obtained in the above Comparative Examples 1 and 2 were confirmed to be homogeneous solutions without any abnormality such as turbidity or precipitation.

[0112] Example 6 The liquid crystal alignment agent (1) obtained in Example 1 was filtered through a filter with a pore size of 1.0 μm, and then applied to a glass substrate with a transparent electrode by a spin coating method. The substrate was dried on a hot plate at 80° C. for 2 minutes, and the coating surface was irradiated with 0.25 J / cm 2 of linearly polarized ultraviolet light having a wavelength of 254 nm and an extinction ratio of 26:1 through a polarizing plate. 2After the irradiation, the coating was baked in a hot air circulating oven at 230° C. for 20 minutes to obtain a substrate with a liquid crystal alignment film having a thickness of 100 nm. The two substrates obtained were combined into a set, and spacers with a diameter of 6 μm were sprayed on the liquid crystal alignment film surface of one of the substrates. A sealant was printed on this substrate, and the other substrate was attached so that the liquid crystal alignment film surfaces faced each other and the alignment direction was 0°, and then the sealant was cured to prepare an empty cell. Liquid crystal MLC-7026-100 (manufactured by Merck) was injected into this empty cell by a reduced pressure injection method, and the injection port was sealed to obtain a liquid crystal cell. When the initial alignment of the liquid crystal cell was confirmed, no flow alignment was confirmed, and the alignment was good. This cell was heat-treated at 120° C. for 60 minutes to prepare a liquid crystal cell.

[0113] [Method for evaluating liquid crystal alignment] The liquid crystal alignment state in the liquid crystal cell prepared by the above procedure was observed using a polarizing microscope (Nikon Corporation, ECLIPSE E600 POL). The liquid crystal alignment was confirmed and there was no flow alignment, and it was judged as "good", and the liquid crystal alignment was not confirmed and there was flow alignment, and it was judged as "bad".

[0114] [Measurement of voltage holding ratio] The liquid crystal cell was aged by placing it on a backlight for 5 days, and then a voltage of 1V was applied for 60μs at 60℃, the voltage was measured after 500ms, and the voltage retention rate was calculated as the voltage retention rate. To measure the voltage retention rate, a VHR-1 made by Toyo Corporation was used. As a result, the voltage holding ratio of the alignment film made of the liquid crystal alignment agent (1) at 60° C. was 61.7%.

[0115] (Examples 7 to 10, Comparative Examples 3 to 4) Liquid crystal cells were prepared in the same manner as in Example 6, except that the liquid crystal alignment agent shown in Table 1 was used instead of the liquid crystal alignment agent (1), and the liquid crystal alignment property and the voltage holding ratio were evaluated. The liquid crystal alignment property and the voltage holding ratio of each of the obtained liquid crystal cells are shown in Table 1.

[0116] [Table 1]

[0117] As shown in Table 1, in Examples 6 to 10 in which additives (T-1) to (T-5) were added, it was confirmed that the voltage holding ratio was improved without a decrease in liquid crystal alignment, compared to Comparative Example 3 in which no additives were added and Comparative Example 4 in which an additive (T-6) different from the aromatic compound of the present invention was added.

[0118] The entire contents of the specification, claims and abstract of Japanese Patent Application No. 2019-184619, filed on October 7, 2019, are hereby incorporated by reference as the disclosure of the specification of the present invention.

Claims

[Claim 1] Any aromatic compound selected from the group consisting of the following formulas (b-1) to (b-4): 【Chemistry 1】

Citation Information

Patent Citations

  • Bismaleimide recipe containing olefin ether modifier

    JP1988023913A

  • composition

    JP1990024309A

  • Polyimide composition

    JP1992306244A

  • Method for orienting liquid crystal

    JP1997297313A

  • Liquid crystal aligning agent, liquid crystal alignment film, and liquid crystal display element

    JP2009109987A